2007
DOI: 10.1002/ajh.20885
|View full text |Cite
|
Sign up to set email alerts
|

Igβ(CD79b) mRNA expression in chronic lymphocytic leukaemia cells correlates with immunoglobulin heavy chain gene mutational status but does not serve as an independent predictor of clinical severity

Abstract: The etiology of chronic lymphocytic leukemia (CLL) is poorly understood and its course is highly variable. Somatic hypermutation (SHM) of the immunoglobulin heavy chain (IgV H ) gene and ZAP70 protein expression have been reported as prognostic indicators. However, these assays are not widely available and their concordance is imperfect. Thus a need exists to identify additional molecular determinants of CLL. The Igb (CD79b) subunit of the B cell antigen receptor is essential for B lymphocyte function. Defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(62 reference statements)
1
2
0
Order By: Relevance
“…By RT-qPCR we were able to demonstrate that the associated mRNAs RALA and RAD51B were similarly differentially expressed, despite the lack of differential expression in the original mRNA microarray data (Figure 8B). The lncRNAs T204050 (FC=3.6), NR_002947 (FC=8.3), and uc.436+ (FC=2.8) have known or nearby protein coding genes implicated in CLL biology [5254]. RT-qPCR expression patterns of all 3 of these lncRNAs were consistent with the microarray data.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…By RT-qPCR we were able to demonstrate that the associated mRNAs RALA and RAD51B were similarly differentially expressed, despite the lack of differential expression in the original mRNA microarray data (Figure 8B). The lncRNAs T204050 (FC=3.6), NR_002947 (FC=8.3), and uc.436+ (FC=2.8) have known or nearby protein coding genes implicated in CLL biology [5254]. RT-qPCR expression patterns of all 3 of these lncRNAs were consistent with the microarray data.…”
Section: Resultssupporting
confidence: 67%
“…Biologically relevant in CLL, the lncRNA NR_002947 and mRNA for its associated protein CD79b were found to be differentially expressed by both microarray and RT-qPCR and displayed opposite expression levels suggesting that CD79b expression may be altered by NR_002947. CD79b is a critical component of the B cell receptor and levels of CD79b mRNA have been shown to be higher in UM CLL even though surface expression of CD79b remains low [52]. However, Guo et al have shown that IL-4 restores CD79b protein expression at the post-transcriptional level and speculated that aberrant expression of micro-RNAs may be playing a role [64].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to normal B cells, B-CLL exhibit low surface expression of Ig and CD79b, associated with low levels of mRNA encoding for CD79b (Thompson et al, 1997). CD79b mRNA level was however found to be higher in the more severe CLL prognostic group associated with unmutated Ig heavy chain variable (V H ) genes (Cajiao et al, 2007), suggesting a possible link between CD79b expression and disease severity. Some authors have compared this BCR-low phenotype to “anergic” B cells which, in animal models, down-modulate surface BCR in response to chronic BCR stimulation by low affinity or soluble self-Ags.…”
Section: Mechanisms Of Pi3k Activation In Malignant B Cellsmentioning
confidence: 99%